AB0142 Sjögren's Syndrome-Associated Transcripts Show Correlation with Objective Measures of Dryness. (15th July 2016) - Ice, J.A.; Adrianto, I.; Rasmussen, A.; Stone, D.U.; Segal, B.M.; Rhodus, N.L.; Radfar, L.; Montgomery, C.G.; Scofield, R.H.; Sivils, K.L.; Lessard, C.J.
Abstract : Background: Sjögren's syndrome (SS) is a chronic autoimmune disorder in which exocrine dysfunction can lead to chronic, debilitating dryness. Expression studies in SS have identified the dysregulated expression of coding and non-coding transcripts enriched in innate and adaptive immune response pathways. Objectives: In our recent SS RNA-seq study, we identified 3748 transcripts showing differential expression (DE; FC>2 or <0.5, q<0.05) in SS patients compared to healthy controls. Of these SS-associated transcripts, [CL1] we sought to identify transcripts whose expression is significantly correlated with objective measures of dryness employed by the 2002 American-European Consensus Group (AECG) classification criteria of SS, including whole unstimulated salivary flow (WUSF), lissamine green (LG) staining, and Schirmer's (Sch) tear migration. Methods: Normalized expression data from a whole blood SS RNA-seq study was obtained for 57 cases and 11 healthy controls who underwent multidisciplinary clinical evaluation for the 2002 AECG classification criteria. Objective dryness measures (WUSF, LG, & Sch) were normalized by log2 transformation and correlation analysis (Spearman for WUSF and LG; Pearson for Sch) was performed for each clinical measure against all of 3748 DE transcripts. Both r or σ and a FDR-corrected p -value, or q -value, were calculated. Significantly correlated transcripts were defined by q <0.05. Results: For WUSF, the significant positive correlation between WUSF rate and the expression of 2 non-coding transcripts was observed: the small Cajal body-specific RNA 5 ( SCARNA5 ; σ=0.50, q =0.018) and the uncharacterized antisense lncRNA RP11–137H2.4 (σ=0.50, q =0.018). For LG, positive correlation was observed for 31 transcripts (0.42<σ<0.51, 0.017< q <0.05) mostly represented by interferon-inducible (IFI) protein-coding genes (e.g. IFIT3, OAS3, and IRF7), although for the pseudogene, ZDHHC4P1, and its neighboring IFI gene EPSTI1 both showed significant positive correlation. For LG, the only negatively correlated transcript was the sodium bicarbonate transporter SCL4A10 (σ= -0.43, q =0.045). For Sch, 3 transcripts ( CARD16, HMGB2, and BLC2A1 ) were negatively correlated (-0.51<σ<-0.49, 0.018< q <0.019), while the transcript IQCH was positively correlated (σ=0.49, q =0.019). Conclusions: We identified SS-associated transcripts whose expression correlates with clinical measures of dryness. For WUSF, the ncRNA SCARNA5 is situated within an intron of the Crohn's disease-associated gene autophagy-related 16-like 1 ( ATG16L1 ). Although IFI genes have previously shown correlation with WUSF, the ZDHHC4P1 pseudogene could regulate neighboring SS-associated IFI gene EPSTI1 . For Sch, CARD16 is a caspase inhibitor that influences apoptotic responses that induces NF-kB activation in inflammation, while BLC2A1 has been shown to slow apoptoic responses. Further transcript characterization will allow us to assess their potentialas biomarkers or surrogates of objective clinical measures for SS. Disclosure of Interest: None declared